Strawberry Pest Management Strategic Plan (PMSP) - Mark A. Mossler; Olaf Norman Nesheim (EDIS)
This circular describes discussions held between Florida strawberry producing stakeholders and pest management professionals in August 2003. The generalized results of the meeting are presented in the executive summary, while specific actions are broken out in the summary at the end of the report. This document is CIR 1443, one of a series of the Pesticide Information Office, Food Science and Human Nutrition Department, Florida Cooperative Extension Service, UF/IFAS. Published February 2004.